Stress and fatigue in sound engineers: the effect of broadcasting in a life show and shift work - Vangelova, Katia K (Central European Journal of Public Health, 2008)
The aim was to study the time-of-day variations of cortisol, fatigue and sleep disturbances in sound engineers in relation to job task and shift work. The concentration of saliva cortisol and feeling of stress, sleepiness and fatigue were followed at three hour intervals in 21 sound engineers: 13 sound engineers, aged 45.1 +/- 7.3 years, broadcasting in a life show during fast forward rotating shifts and 8 sound engineers, aged 47.1 +/- 9.8 years, making records in a studio during fast rotating day shifts. Cortisol concentration was assessed in saliva with radioimmunological kits. The participants reported for stress symptoms during the shifts and filled sleep diary. The data were analyzed by tests of between-subjects effects (SPSS). A trend for higher cortisol was found with the group broadcasting in a life show. The sound engineers broadcasting in a life show reported higher scores of stress, sleepiness and fatigue, but no significant differences concerning the sleep disturbances between the groups were found. In conclusion our data show moderate level of stress and fatigue with the studied sound engineers, higher with the subjects broadcasting in a life show. The quality of sleep showed no significant differences between the studied groups, an indication that the sound engineers were able to tolerate the fast forward rotating shifts.
Keywords: hromadné sdělovací prostředky; lidé středního věku; Circadian Rhythm; Personnel Staffing and Scheduling; lidé; sliny; Fatigue; Stress, Psychological; vliv směnného provozu na zdraví; personální obsazení a rozvrh; Work Schedule Tolerance; psychický stres; Dyssomnias; hydrokortison; cirkadiánní rytmus; únava; Occupational Diseases; Hydrocortisone; nemoci z povolání; dyssomnie; Middle Aged; Saliva; Humans; Mass Media